Nursing Management Implementation and Burnout Syndrome as Predictors of Nursing Care Quality - Firnawati, Derlin; Wardani, Ratna; Nurwijayanti, Nurwijayanti (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The quality of nursing care in hospitals is influenced by multiple organizational and psychological factors, particularly the implementation of nursing management and the presence of burnout syndrome among nurses. Effective nursing management ensures coordinated care delivery, while burnout may reduce professional performance and service responsiveness. This study aimed to analyze the implementation of nursing management and the effect of burnout syndrome on the quality of nursing care. A cross-sectional design was employed involving 98 respondents. Data were collected using structured questionnaires, and hypotheses were tested using multiple linear regression analysis to examine the simultaneous and partial effects of nursing management and burnout syndrome on nursing service quality. The analysis demonstrated that nursing management had a significant effect on the quality of nursing care (p = 0.027; t = 2.242). Burnout syndrome also showed a significant effect on nursing service quality (p = 0.005; t = 2.899). These findings indicate that both organizational management practices and psychological conditions significantly influence service quality. As conclusion, nursing management implementation and burnout syndrome are the predictors of nursing care quality. Strengthening managerial practices and addressing nurse burnout are essential strategies to improve hospital service quality.Keywords: nursing management; burnout syndrome; service quality; nurses